Classification of methods of gases purification from hydrogen sulfide - Слюзар, А. В.; Калимон, Я. А.; Буклів, Р. Л.; Slyuzar, A.; Kalymon, Ya.; Bukliv, R. (Lviv Politechnic Publishing House, 2018)
Описано існуючі класифікації способів очищення газів від сірководню. Показано їх переваги та недоліки. Запропоновано класифікувати методи очищення газів за суттю фізико-хімічних взаємодій сірководню під час його уловлення – конверсійні і неконверсійні. У результаті неконверсійних процесів одержують концентрований сірководеньвмісний газ, який потребує подальшої переробки чи утилізації. Конверсійні методи дають змогу одержати сірку чи інші сульфуровмісні продукти під час окиснення чи розкладу сірководню.

The existing classifications of methods for purifying gases from hydrogen sulfide is described. Their advantages and disadvantages are shown. It is proposed to classify the methods by nature of physicochemical interactions of hydrogen sulfide during its removal – conversion and non-conversion. As a result of non-conversion processes, concentrated hydrogen sulfide – containing gas is produced, which requires further processing or utilization. Conversion methods allow sulfur or other sulfur-containing products to be produced during the oxidation or decomposition of hydrogen sulfide.
Класифікації методів очищення газів від сірководню
Keywords: очищення газів; сірководень; класифікації методів; gases purification; hydrogen sulfide; classifications of methods; 66.074.5